Do job crafting opportunities help to win talent? Disentangling and contextualizing the effects of job crafting opportunities on applicant attraction - Jens Schüler; Sonja Franzke; Philipp Boehnlein; Matthias Baum (Journal of Organizational Behavior, 2023)
We argue that job crafting opportunities are not only helpful to motivate and enable the existing workforce but that they can also function as a signal to attract talent. With the help of two empirical studies (Study 1 – a conjoint experiment and Study 2 – a vignette study), we show that (a) a signaled opportunity for job crafting helps to attract job seekers; (b) job crafting signals can trigger positive as well as negative expectations of central job demands and resources that inform job acceptance intentions, and; (c) a proactive personality strengthens most of the positive expectations of job crafting signals while buffering adverse effects.
Keywords: 650; applicant attraction; job crafting opportunities; signaling theory